BUDAYA DAN ETIKA BISNIS MASYARAKAT JEPANG - Budi Mulyadi (Diponegoro University, 2017)
The title of this article is The Cullture and The Ethics of Businessu in Japanese Society. The main purpose of this paper writing is to describe about is The Cullture and The Ethics of Businessu in Japanese Society. This article writing uses field reserach. Main method are observation, and interpretation. This article explains The Cullture and The Ethics of Businessu in Japanese Society are influenced by basic Japanese character. Some examples for basic Japanese character are dicipline, hard work, honest etc. Japanese businessuman pays attentioan in ethics of businnesu. There are 3 ethisc of businessu that must be attentive when doing businnesu with Japanese people. They are ethic get acquainted, ethics correspond, ethics of maintaning businessu relationship.